Leveraging Arts for Justice, Equity, and Public Health: The Skywatchers Program and Its Implications for Community-Based Health Promotion Practice and Research. (May 2021) - Epstein, Rabbi Nancy E.; Bluethenthal, Anne; Visser, Deirdre; Pinsky, Clara; Minkler, Meredith
Arts have long addressed the conditions that cause ill health, such as poverty, social inequality, and structural racism, and have recently taken on increased significance for public health. This article illuminates the potential for cross-sector collaboration between community-based health promotion and community-engaged arts to address the social determinants of health and build neighborhood assets at multiple levels of the social-ecological model. It features Skywatchers, a collaborative community arts ensemble of artists and residents of the culturally rich but economically poor Tenderloin neighborhood in San Francisco, California, and its original values-based "relational, durational, conversational, and structural" methodology focused on process over product and leveraging arts for justice and equity. Now, 10 years into its work, Skywatchers offers lessons about building reciprocal relationships, cocreating artworks, and promoting arts-based advocacy to improve the conditions that foster poor health in the neighborhood. The article discusses implications for community-based health promotion practice that delineate commitments and challenges shared between the two fields, their distinct roles and tools, and the potential for more widespread partnerships. It concludes with implications for policy and advocacy and a vision for expanded community-based participatory research to better understand the impact of arts on community health and well-being.